Stevenleaf from Gynostemma Pentaphyllum inhibits human hepatoma cell (HepG2) through cell cycle arrest and apoptotic induction - Sayed Sajid Hussain; Fan Zhang; Yuanyuan Zhang; Kiran Thakur; Mahrukh Naudhani; Carlos L. Cespedes-Acuña; Zhaojun Wei (Food Science and Human Wellness)
The anticancer activity of stevenleaf (SV) on the basis of cell viability, cell cycle, and apoptosis induction in HepG2 cancer cells were evaluated. SV controlled the growth of HepG2 cells with IC50 of 139.82 μmol/L for 24 h, IC50 of 119.12 μmol/L for 48 h and cell cycle arrested at G0/G1 phase, induced cell apoptosis and enhanced intracellular ROS generation. For cell cycle arrest, the mRNA expression levels of p21, p27 and p53 were up-regulated, while the expression levels of Cyclin A, Cyclin D1, Cyclin E and CDK1/2 were down-regulated. SV efficiently up-regulated TNF R1, TRADD1 and FADD and down-regulated Caspase8 for cell death receptors; similarly, up-regulated Bax, Bak, Cyt c, Apaf1, Caspase3 and Caspase9, and down-regulated Bcl2, Bcl xl and Bad for mitochondrial signal pathway. SV induced the mTOR-mediated cell apoptosis in HepG2 cells via activation of Akt and AMPK. The mechanistic explanation for the anticancer activity of SV as functional food can be derived from above results.